Deconstruction of the Legend “Putri Tujuh”: Reproduction of the Meaning of Marriage Hierarchy in Contemporary Malay Society - Elmustian; Ika Apriyanti (International journal of technology and education research, 2026)
Folktales are often viewed as static entities that serve only as conservative didactic media. This study aims to deconstruct the legend of